Combining ultrasound, vacuum and/or ethanol as pretreatments to the convective drying of celery slices - Miano A.C. (2021)
The authors are grateful to the Programa Nacional de Investigación Científica y Estudios Avanzados (PROCIENCIA) from the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica” (CONCYTEC, Peru) for funding the project n° 409-2019-FONDECYT, to the Universidad Privada del Norte (UPN, Peru) for funding the project n° 20201005, to the Săo Paulo Research foundation (FAPESP, Brazil), for funding the project n° 2019/05043-6, and the National Council for Scientific and Technological Development (CNPq, Brazil), for funding the productivity grant of PED Augusto (310839/2020-3).